Link between molecular mobility and order parameter during liquid–liquid transition of a molecular liquid - Murata, Ken-ichiro (Proc Natl Acad Sci U S A, 2019)
Liquid–liquid transition (LLT) is the transformation of one liquid to another via first-order phase transition. For example, LLT in a molecular liquid, triphenyl phosphite, is macroscopically the transformation from liquid I in a supercooled state to liquid II in a glassy state. Reflecting the transformation from the liquid to glassy state, the LLT is accompanied by considerable slowing down of overall molecular dynamics, but little is known about how this proceeds at a molecular level coupled with the evolution of the order parameter. We report such information by performing time-resolved simultaneous measurements of dielectric spectroscopy and phase contrast microscopy/Raman spectroscopy by using a dielectric cell with transparent electrodes. We find that the temporal change in molecular mobility crucially depends on whether LLT is nucleation growth type occurring in the metastable state or SD type occurring in the unstable state. Furthermore, our results suggest that the molecular mobility is controlled by the local order parameter: more specifically, the local activation energy of molecular rotation is controlled by the local fraction of locally favored structures formed in the liquid. Our study sheds light on the temporal change in the molecular dynamics during LLT and its link to the order parameter evolution.